A influência do patrocinador no sucesso de projetos: um estudo de caso - Santos, Marcelo Alves (2017)
The analysis of critical factors for project success, as well as the definition of success in projects, are contents that are constantly addressed in the project management literature. This case study proposed a clipping in this subject, focusing on how the project sponsoring executive can contribute to the success of a project. Two projects within the same organization were analyzed, applying the theory developed by KLOPPENBORG et Al. (2014) for evaluating behaviors of the project sponsor. For each project interviews were conducted with closed questions, followed by open questions with their respective stakeholders. The objective of these interviews was to understand how the project sponsor contributed to the success of the projects studied through the theoretical lens adopted. Using a qualitative methods this research has indicated that the project sponsor had a major impact on the success of the projects chosen. The research indicated that the following behaviors contributed to the result of the projects in the organization: (1) behavior 3 - the project sponsor guaranteed the project planning; (2) behavior 6 - the project sponsor maintained a relationship with the stakeholders; (3) behavior 7 - The project sponsor ensured communication between the project and its stakeholders. The emergence of responses through qualitative research also allowed exploring other factors that influence success, but will not be discussed in depth in this research. This work aims to contribute to the body of knowledge about project management exploring the sponsor's impact on project success. At the same time it also aims to encourage organizations to rediscuit the role of the project sponsor by allowing them to contribute positively to the success of projects within organizations.